Spatial distribution of uptake of newly introduced vaccines and its associated factors among children aged 12–35 months in Ethiopia: Multi-scale Geographically Weighted Regression Analysis - Habtamu Guaguahu Feleke; Mulat Belay Simegn; Daniel Tarekegn Worede; Werkneh Melkie Tilahun (PLoS ONE, 2026)
Background The pneumococcal conjugate vaccine (PCV) and rotavirus vaccine (RVV) have been introduced to Ethiopia’s expanded childhood immunization program in 2011 and 2013, respectively. Methods A cross-sectional study among 2,055 children aged 12–35 months was employed. Data were extracted from the Kids Record file of the 2019 Ethiopian Mini Demographic and Health Survey. Spatial regression models were fitted and compared using corrected Akaike Information Criteria, Bayesian Information Criteria and adjusted R 2 . Spatial predictors were determined to be statistically significant if their p-value was < 0.05. Results Incomplete uptake of recently introduced immunizations was observed in nearly half (48.83%) of children aged 12–35 months. Its distribution throughout Ethiopia’s regions shows significant spatial clustering, with the eastern part of SNNPR and Somali regions having hot spots. A total of 3 significant clusters, located in southern Oromia, east and west Hararge, the entire SNNPR, and the majority of the Somali region, with a high rate of incomplete uptake of newly introduced vaccines, were identified during SaTScan analysis. Not having vaccination cards, household size more than 5 members, home delivery, not having postnatal care, and less than 18 maternal age at first birth are positive significant spatial factors while parents not being head of the household were identified as negative significant spatial factors. Conclusion There is high incomplete uptake and spatial disparities of PCV and RVV. To improve vaccination coverage among children aged 12–35 months, policymakers and health planners should prioritize targeted interventions in hotspot areas, strengthen maternal health service utilization, and enhance vaccination tracking systems. Promoting community awareness and improving access to essential health services will be critical to ensuring equitable immunization uptake across the country.